Impact of Cognitive Functioning on the Mentoring Relationships between International Graduate Students and their Academic Advisors - Geovani Ayala; James C. Anderson II; Shreya Mitra (Journal of International Agricultural and Extension Education, 2025)
International study is essential in developing diverse and well-rounded global citizens who will become the next generation of world leaders. International study equips students with the skills to address the world’s most pressing and complex problems. An integral factor in the success of international graduate students is the relationship dynamic with their faculty advisor. The faculty-graduate student mentoring relationship is crucial for academic and personal success and professional development (Lim et al., 2021; Woo et al., 2015). The role of faculty advisors with international students has expanded from traditional supervisory roles to include roles as translators, confidants, and pillars for social integration (Marijanovic et al., 2021; Woo et al., 2015). In this study, we hypothesize that cognitive differences, more than cultural differences, affect the productivity of this problem-solving dyad. This study investigated the lived experiences of international graduate students related to the development of and satisfaction with the faculty-student mentoring relationship. Findings show that besides cultural intelligence, clear expectations, mutual respect, and flexibility contributed to international students' perceived satisfaction with the mentoring relationship.
Keywords: Mentorship; Advising; Faculty; Graduate Students; Problem Solving; Emotional Intelligence